Mechanisms of Neuroinflammation - Emiliano Aranda Abreu, Gonzalo (IntechOpen, 2017)
"Mechanisms of Neuroinflammation" book explains how the neuronal cells become swollen at the moment of the blood-brain barrier disruption and how they lose their immunological isolation. A cascade of cytokines and immune cells from the bloodstream enters the nervous system, inflaming neurons and activating the glia. This produces a neuroinflammatory process that can generate different neurodegenerative diseases. Better understanding of mechanisms that are activated at the time when the damage to the brain occurs could lead to the development of suitable therapies that revert the neuronal inflammation and thus prevent further damage to the nervous system.